Effect of physical properties of germination substrate on marigold (Tagetes erecta L.) seedling growth - Asyhuriyah Wardah Defitrianida (Journal of Agrosociology and Sustainability, 2026)
Background: Marigold (Tagetes erecta L.) is a herbaceous plant widely cultivated for ornamental and ecological purposes. Its cultivation is strongly influenced by environmental factors, especially nutrient availability in the growing media. This study aimed to examine the effect of different seedling media compositions on their physical properties and the growth of marigold (Tagetes erecta L.) seedlings. Previous studies suggest that the physical properties of seedling media, such as porosity and water-holding capacity, play a crucial role in early plant development. Methods: The experiment was conducted using a Completely Randomized Block Design (RCBD) with one factor—media composition. The treatments included M0 (ready-to-use commercial media), M1 (husk charcoal [2]: cocopeat [1]: bamboo compost [1]), M2 (husk charcoal [1]: cocopeat [2]: bamboo compost [1]), and M3 (husk charcoal [1]: cocopeat [1]: bamboo compost [2]). Data collection included plant height, number of leaves, root length, number of roots, fresh weight, and dry weight. Data were analyzed statistically to determine the significance of treatment effects. Findings: The composition of the growing media significantly influenced marigold seedling growth. Media with a higher proportion of cocopeat (M2) resulted in greater porosity, which in turn supported better seedling development. This was evidenced by higher values in plant height, number of leaves, root length, root count, fresh biomass, and dry biomass compared to other treatments. Conclusion: The study concludes that the M2 media composition (husk charcoal [1]: cocopeat [2]: bamboo compost [1]) provides optimal physical conditions for marigold seedling growth. Novelty/Originality of this article: This research offers new insights into the effect of media physical properties on marigold seedling performance, particularly highlighting the beneficial role of increased cocopeat content in enhancing media porosity and seedling growth.